Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1159/000151569
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C- and Reactive Oxygen Species-Dependent Stimulation of Intracellular cAMP in Human Eosinophils

Abstract: Objective: The objective of this study was to investigate the role of the extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) in the signalling pathway of the novel protein kinase C (PKC)- and reactive oxygen species (ROS)-dependent stimulation of intracellular adenosine 3′,5′-cyclic monophosphate (cAMP) production in human eosinophils. Materials and Methods: Immunomagnetically purified human eosinophils were stimulated in vitro with a PKC activator, phorbol myristate acetate (PMA), and the cAMP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Ezeamuzie et al. found that PD98059 inhibited the PMA‐induced production of cAMP, and suggested a signalling pathway with ERK1/ERK2 located downstream of PKC, and where the end product was cAMP (41). This hypothesis could thus explain the increased degranulation caused by staurosporine, GÖ6976 and PD98059; however, it remains to be proven that this is the pathway elicited by C3b and serum‐opsonized Sephadex particles.…”
Section: Discussionmentioning
confidence: 99%
“…Ezeamuzie et al. found that PD98059 inhibited the PMA‐induced production of cAMP, and suggested a signalling pathway with ERK1/ERK2 located downstream of PKC, and where the end product was cAMP (41). This hypothesis could thus explain the increased degranulation caused by staurosporine, GÖ6976 and PD98059; however, it remains to be proven that this is the pathway elicited by C3b and serum‐opsonized Sephadex particles.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been described recently (Ezeamuzie and Taslim, 2008). In brief, fresh blood was obtained from consenting individuals who were mildly atopic, but had no allergic disease nor taken any medication in the last 72 h. The protocol for the study was reviewed and approved by the Ethics Committee of the Faculty of Medicine, Kuwait University, Kuwait.…”
Section: Isolation Of Blood Eosinophilsmentioning
confidence: 99%
“…This was done using a method recently reported (Ezeamuzie and Taslim, 2008). In brief, eosinophils, re-suspended at a concentration of 10 7 cells/ml in BSA-free reaction buffer, were dispensed in 50 μl aliquots into each well of a 96-well plate.…”
Section: Intracellular Cyclic Amp Determinationmentioning
confidence: 99%
“…The cAMP stimulation results in the up-regulation of microphthalmia-associated transcription factor (MITF), tyrosinase, and tyrosinase-related proteins (Tyrp1 and Tyrp 2) 5 6 7 . The stimulation of cAMP can be affected by several factors such as adrenocorticotropic hormone (ACTH), prostaglandin E2 (PGE2), and alpha-melanocyte stimulating hormone (α-MSH) 3 4 8 9 . The increase in melanogenesis without affecting the skin is very important, because it can protect the skin from diseases such as cancer 10 and vitiligo 11 .…”
mentioning
confidence: 99%